BIOLOGICAL ASPECTS AND CONSERVATION OF Rafflesia arnoldii : INDONESIAN ENDEMIC PLANT CONSERVATION - Angga Puja Asiandu (Konservasi Hayati, 2021)
Rafflesia arnoldii is one of the rare endemic plants in Indonesia. This endemic plant has unique characteristics and has various kinds of modifications that differentiate it from other plants. However, this largest-flower plant is classified as an endangered plant. It is due to its limited life cycle and distribution area. Many kinds of habitat destruction caused by human activities also threaten the existence of this endemic plant. Besides, it is highly dependent on the presence of its host plant, Tetrastigma sp. Therefore, conservation actions are needed. Conservation is implemented through in-situ or ex-situ conservation. It can be optimized by utilizing ecotourism activities that involve local communities.